Expression and clinical significance of Cathepsin K and MMPs in invasive non-functioning pituitary adenomas - Liu, Hongyan; Zhang, Saichun; Wu, Ting; Lv, Zhaohui; Ba, Jianming; Gu, Weijun; Mu, Yiming (Frontiers in Oncology, 2022)
Background Cathepsin K (CTSK) is a protease that degrades type I collagen and extracellular matrix, thereby contributing to bone resorption and tumor invasion. Some pituitary adenomas (PAs) could invade the sphenoid sinus (SS) and cavernous sinus (CS). Purpose This retrospective cohort study aimed to study the expression of tumoral biomarkers (CTSK, MMP9, MMP2, TIMP2, and PTTG1) and evaluate their clinical significance in non-functioning pituitary adenomas (NFPAs) with different invasion patterns. Methods We assessed the expression levels of candidate invasion-specific protein biomarkers CTSK, MMP9, MMP2, TIMP2, and PTTG1 by immunohistochemical staining in paraffin-embedded NFPA tumor tissues. Variations in staining intensity were analyzed in cases with SS and CS invasion and non-invasive NFPAs. Results We found that the levels of CTSK were higher in PA cases with SS invasion than that in PA cases with CS invasion (95.57 ± 31.57 vs. 65.29 ± 29.64, P < 0.001), and the expression of MMP9 and MMP2 was higher in CS-invasive cases than that in SS-invasive cases (145.02 ± 49.25 vs. 111.80 ± 51.37, P = 0.002, and 138.67 ± 52.06 vs. 108.30 ± 41.70, P = 0.002). Multiple Cox regression demonstrated that higher CTSK expression (P=0.011), subtotal resection (P<0.001), invasion (P=0.037), and larger tumor diameter (P=0.001) were independent risk factors for recurrence. A positive correlation was observed between CTSK expression and tumor size (r=0.671, p<0.001). There was no significant difference in TIMP2 and PTTG1 levels between CS-and SS-invasive cases (97.42± 39.80 vs. 102.10± 43.22, P = 0.58 and 13.89 ± 4.59 vs. 12.56 ± 3.96, P = 0.14). Conclusion Our data indicated that CTSK has the potential as a marker for SS invasion of PAs, whereas MMP9 and MMP2 may be markers for CS invasion. And CTSK may play an important role in tumor relapse.